The Effect Of Solvency, Liquidity, Sales Growth And Asset Management On Financial Performance - Artanti, Anggun; Maula, Kholida Atiyatul; Lestari, Kamini (Peneliti.net, 2025)
This research aims to examine the influence of solvency, liquidity, sales growth and asset management on financial performance. Data analysis in this research uses multiple linear regression analysis and the sample selection method used in this research is the purposive sampling method. The sample used in this research is all retail trading subsector companies listed on the Indonesia Stock Exchange during the 2018-2022 period with a total of 40 observation data. The research results show that partially sales growth has a significant positive effect on financial performance, asset management has a negative effect on financial performance. Meanwhile, solvency and liquidity have no effect on financial performance. Meanwhile, simultaneously all independent variables have a significant effect on financial performance.